2015
DOI: 10.1002/cplu.201500042
|View full text |Cite
|
Sign up to set email alerts
|

A Chalcone‐Based Highly Selective and Sensitive Chromofluorogenic Probe for Trivalent Metal Cations

Abstract: ElsevierCliment Olmedo, MJ.; Corma Canós, A.; Hernández, JC.; Hungría, AB.; Iborra Chornet, S.; Martínez Silvestre, S. (2012). Biomass into chemicals: One-pot two-and three-step synthesis of quinoxalines from biomass-derived glycols and 1,2-dinitrobenzene derivatives using supported gold nanoparticles as catalysts. AbstractAn efficient and selective one-pot two steps, method for the synthesis of quinoxalines by oxidative coupling of vicinal diols with 1,2-phenylenediamine derivatives, has been developed by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…For Fe 3+ detection, numerous probes have been recently reported. For instance, Lee et al have reported a selective rhodamine-based sensor showing a sensitive and selective detection of intracellular Fe 3+ ions in hepatocytes. , To the best of our knowledge, Kim and co-workers were the first in synthesizing an indium sensor, based on pyrene moieties . Due to the high interest of monitoring In 3+ concentrations in biological environments, the number of optical probes for In 3+ detection is also increasing. Nevertheless, the design of new chemosensors able to quantify the cellular concentrations of iron and indium ions is still needed for the fundamental understanding of indium toxicity as well as for the diagnosis of associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For Fe 3+ detection, numerous probes have been recently reported. For instance, Lee et al have reported a selective rhodamine-based sensor showing a sensitive and selective detection of intracellular Fe 3+ ions in hepatocytes. , To the best of our knowledge, Kim and co-workers were the first in synthesizing an indium sensor, based on pyrene moieties . Due to the high interest of monitoring In 3+ concentrations in biological environments, the number of optical probes for In 3+ detection is also increasing. Nevertheless, the design of new chemosensors able to quantify the cellular concentrations of iron and indium ions is still needed for the fundamental understanding of indium toxicity as well as for the diagnosis of associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there are relatively few probes able to detect simultaneously several trivalent cations [9][10][11][12][13][14][15][16][17][18][19] and we have found in the literature only one probe that recognizes Al 3+ , Fe 3+ , Cr 3+ , As 3+ , In 3+ and Ga 3+ at the same time. 20 Moreover, most probes for trivalent cations display sensing features in organic solvents and it is rare to find probes for these cations in pure water. 21 Taking into account these facts, and our experience in the synthesis of molecular and material-based sensors for the optical recognition of chemical species, 22 we report herein the synthesis, characterisation and chromo-fluorogenic behavior toward cations of the chalconebased probe 3.…”
mentioning
confidence: 99%
“…Exposure can also occur through skin contact with soil or water containing arsenic. 20 Moreover, most probes for trivalent cations display sensing features in organic solvents and it is rare to find probes for these cations in pure water. 21 Taking into account these facts, and our experience in the synthesis of molecular and material-based sensors for the optical recognition of chemical species, 22 we report herein the synthesis, characterisation and chromo-fluorogenic behavior toward cations of the chalconebased probe 3.…”
mentioning
confidence: 99%
“…The emission intensity of [H 2 L−Zn 2+ ] in the presence of Fe 3+ , Al 3+ , and Cr 3+ exhibits slight interferences. This may be due to the weak secondary interaction among the molecular assembly of [H 2 L−Zn 2+ ] and M 3+ (Fe 3+ , Al 3+ , Cr 3+ ), 71,72 while for other cations, the emission is almost unaffected and interestingly, the probe could detect Zn 2+ even in the presence of Cd 2+ and Hg 2+ (Fig. S10†).…”
Section: Resultsmentioning
confidence: 99%